Bilateral Iridocorneal Endothelial Syndrome - Theresa Gladiola B. Merca, MD; Manuel B. Agulto, MD; Rainier Victor A. Covar, MD, MMed (Philippine Journal of Ophthalmology)
Objectives: We presented a case of bilateral iridocorneal endothelial (ICE) syndrome with secondary glaucoma and discussed its clinical presentation and management.